Quality of Life of Geriatrics Patient Suffering from Hypertension with Diabetes Mellitus Comorbid and Factors that Influence It - Vania Fitriana; Ragil Setia Dianingati; Eva Annisaa (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Elderly people are susceptible to degenerative diseases such as hypertension. Hypertension with comorbidities is one of the leading causes of death worldwide. One of the comorbidities of hypertension is diabetes mellitus. Hypertension with comorbidities can cause serious symptoms. Elderly also prone to decreased physical function, which can decrease their independence in performing daily activities, thus can affect their quality of life. Objective: To understand the characteristics, daily activities independence, polypharmacy prescribing, quality of life, and the relationships between characteristics, independence in daily activities, number of medications consumed, and quality of life in geriatric patients with hypertension and comorbid diabetes mellitus at RSD K.R.M.T Wongsonegoro Semarang. Methods: This was a descriptive study with a cross-sectional approach was employed. The instruments used the WHOQOL-BREF and Katz Index questionnaire. The questionnaire was directly given to the patients. Results: From 75 respondents, the majority were female (61.3%), had a normal BMI (53.3%), had low-moderate education (70.7%), were married (54.7%), had high independence (93.3%), and received polypharmacy prescriptions (89.3%). Conclusion: There is a relationship between gender, BMI, marital status, and daily activity independence with the quality of life of patients. However, there is no relationship between education level and the number of medications consumed with the quality of life of patients. The factor that most influences quality of life is independence in daily activities.